The cognitive engineering of memory in educational website design - Jones, Jessica; Fitzpatrick, Jill; Chassy, Philippe (Advances in Social Sciences Research Journal, 2015)
The ability to recall items from memory is often vital, whether for remembering a phone number, or when sitting an examination. Memory also affects our aesthetical judgements of objects, and the ways in which we perceive such objects as complex or simple. The role of memory likewise extends to our interactions with computer technology; influencing our overall experience of websites, the processing of information provided by websites and thus the quality of our learning processes. For many people, the internet is their primary source of information, and hence websites designed to facilitate learning should be designed in line with the cognitive architecture of the user. This paper exposes the main components of human memory, outlining its limits. We then consider the role of three memory-related factors: prototypicality, visual complexity, and aesthetics, on the user’s interaction with a website. A key point of the present article is that websites should be designed with consideration to the constraints of human memory. Finally, we emphasise how such limits should be respected, and how effectively capitalising on the memory structure of the user should aid efficient learning.